Determinants of Watching a Film: A Case Study on Dhallywood Film Industry, Bangladesh - Easmin, Mst. Farjana; Hossain, Afjal; Mandal, Anup Kumar (Asian Business Review, 2018)
The purpose of the study is to classify the different factors influencing the success of a Bengali film, and in this regard, a total sample of 296 respondents has been interviewed through a structured questionnaire. To test the study, Pearson’s product moment correlation, ANOVA and KMO statistic has been used and factor analysis is used to group the factors needed to develop for producing a successful film. The study reveals that the first factor (named convenient factor) is the most important factor for producing a film as well as to grab the attention of the audiences by 92% and competitive advantage by 71%, uniqueness by 81%, supports by 64%, features by 53%, quality of the film by 77% are next consideration consecutively according to the general people perception. The implication of the study is that the film makers and promoters should consider the factors properly for watching more films of the Dhallywood industry in relation to the foreign films especially Hindi, Tamil and English. The government can also take the initiative for the betterment of the industry through proper governance and subsidize if possible.